2020
DOI: 10.1101/2020.11.26.400515
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Centromere drive and suppression by parallel pathways for recruiting microtubule destabilizers

Abstract: SummarySelfish centromere DNA sequences bias their transmission to the egg in female meiosis. Evolutionary theory suggests that centromere proteins evolve to suppress costs of this “centromere drive”. In hybrid mouse models with genetically different maternal and paternal centromeres, selfish centromere DNA exploits a kinetochore pathway to recruit microtubule-destabilizing proteins that act as drive effectors. We show that such functional differences are suppressed by a parallel pathway for effector recruitme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
2

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 97 publications
(155 reference statements)
0
8
0
Order By: Relevance
“…Evidence for this coevolution model has emerged from engineering "evolutionary mismatches" between the chromatin protein(s) of one species and the DNA satellite landscape of a close relative. Under one approach, a diverged chromatin protein is introduced into a closely related species, generating an evolutionary mismatch between the manipulated protein and one or more DNA satellites [14][15][16][17]. Consistent with disrupted DNA satellite:chromatin protein coevolution, the naïve chromatin protein typically perturbs a satellite-mediated function, such as chromosome segregation or nuclear organization [14,16,17].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Evidence for this coevolution model has emerged from engineering "evolutionary mismatches" between the chromatin protein(s) of one species and the DNA satellite landscape of a close relative. Under one approach, a diverged chromatin protein is introduced into a closely related species, generating an evolutionary mismatch between the manipulated protein and one or more DNA satellites [14][15][16][17]. Consistent with disrupted DNA satellite:chromatin protein coevolution, the naïve chromatin protein typically perturbs a satellite-mediated function, such as chromosome segregation or nuclear organization [14,16,17].…”
Section: Resultsmentioning
confidence: 99%
“…Under one approach, a diverged chromatin protein is introduced into a closely related species, generating an evolutionary mismatch between the manipulated protein and one or more DNA satellites [14][15][16][17]. Consistent with disrupted DNA satellite:chromatin protein coevolution, the naïve chromatin protein typically perturbs a satellite-mediated function, such as chromosome segregation or nuclear organization [14,16,17]. In these cases, however, the incompatible DNA satellites are unknown.…”
Section: Resultsmentioning
confidence: 99%
“…The kinetochore pathway (discussed above) functions through kinetochore recruitment of BUB1 [38,53,54]. Independently, the CPC can localize to pericentromeric heterochromatin and recruit SGO2 and MCAK in the heterochromatin pathway [58][59][60][61]. Kumon et al suggest that evolutionary shifts which lead to less reliance on the kinetochore pathway and more reliance on the heterochromatin pathway is a route for genome suppression of centromere drive [58].…”
Section: Role Of the Pericentromere In Centromere Drivementioning
confidence: 99%
“…Independently, the CPC can localize to pericentromeric heterochromatin and recruit SGO2 and MCAK in the heterochromatin pathway [58][59][60][61]. Kumon et al suggest that evolutionary shifts which lead to less reliance on the kinetochore pathway and more reliance on the heterochromatin pathway is a route for genome suppression of centromere drive [58]. Conversely, it is possible that centromeric and pericentromeric DNA function selfishly as one unit and manipulate their pericentromere to recruit more destabilizing factors.…”
Section: Role Of the Pericentromere In Centromere Drivementioning
confidence: 99%
“…guttatus might have been selected to disfavor binding to D , thereby suppressing centromere drive. Indeed, centromere-binding proteins with low centromeric affinity can weaken meiotic drive in mice [ 13 ]. The relative affinity of Mimulus CenH3A proteins for satellites between competing centromeres could explain why this new study found no straightforward hierarchy in CenH3A allele combinations and drive suppression in the new study.…”
mentioning
confidence: 99%